POLA SENSITIVITAS ANTIBIOTIK PADA PENYAKIT MUSKULOSKELETAL DI RUMAH SAKIT ORTHOPEDI DAN TRAUMATOLOGI SURABAYA - Nabila Ananda Kloping; David Nugraha; Andro Pramana Witarto; Komang Agung Irianto (Atma Jaya Catholic University of Indonesia, 2020)
Introduction: Indiscriminate use of antibiotics contributes to the increasing resistance of more than one type of bacterias. Research on new antibiotic therapies and agents cannot keep up with the rapid antibiotic resistance. This study aimed to describe the patterns of antibiotic sensitivity and resistance at the Orthopedic and Traumatology Hospital (RSOT) Surabaya. Methods: This was a cross-sectional descriptive study. Secondary data from medical records year 2016-2018 were retrieved from patients treated at RSOT Surabaya who received antibiotic therapy. Only those with data of antibiotic sensitivity test results were included Results: The sensitivity test results of all b-lactamase inhibitors and cephalosporin antibiotics showed a decrease in sensitivity each year with a variety of coverage patterns. The fluoroquinolone group had increased sensitivity during the observation period. Conversely, a reduction in gentamicin sensitivity was followed by an increase in the resistance. This increase in resistance was also observed in meropenem with various sensitivity patterns. Linezolid sensitivity increased, while the sensitivity of teicoplanin remained 100.00%. Conclusion: There is no particular pattern in antibiotic sensitivity and bacterial resistance in RSOT Surabaya, except for cephalosporin, which shows a rising resistance and a decrease in sensitivity each year.